2006
DOI: 10.1021/ja061137d
|View full text |Cite
|
Sign up to set email alerts
|

Single Quantum Dot-Micelles Coated with Silica Shell as Potentially Non-Cytotoxic Fluorescent Cell Tracers

Abstract: The present study describes a stabilization of single quantum dot (QD) micelles by hydrophobic silica precursors and an extension of the silica layer to form a silica shell around the micelle. The obtained product consists of up to 92% of single nanocrystals (CdSe, CdSe/ZnS, or CdSe/ZnSe/ZnS quantum dots) in the silica micelles, coated with silica shell. The thickness of silica shell could vary, starting from 3 to 4 nm. Increasing the shell thickness increases the photoluminescent characteristics of QDs in aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
174
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 253 publications
(179 citation statements)
references
References 9 publications
5
174
0
Order By: Relevance
“…Meanwhile, the emission peak intensity of poly (BImBHCS-X) (X" = Br", BF 4 ", PF 6 " and TFSI") was much stronger than that of PBBHCS. This indicated that the counter-anions inserted into the polymer samples hindered the strong high-ordering packing of the side chain biphenyl mesogens, which resulted in the absence of fluorescence quenching [66][67][68][69]. The fluorescence emission spectra results were consistent with the previous results describing the structures of the MCSC-ILCPs poly(BImBHCS-X).…”
Section: The Photophysical Properties Of Mcsc-ilcps Poly(bimbhcs-x)supporting
confidence: 88%
“…Meanwhile, the emission peak intensity of poly (BImBHCS-X) (X" = Br", BF 4 ", PF 6 " and TFSI") was much stronger than that of PBBHCS. This indicated that the counter-anions inserted into the polymer samples hindered the strong high-ordering packing of the side chain biphenyl mesogens, which resulted in the absence of fluorescence quenching [66][67][68][69]. The fluorescence emission spectra results were consistent with the previous results describing the structures of the MCSC-ILCPs poly(BImBHCS-X).…”
Section: The Photophysical Properties Of Mcsc-ilcps Poly(bimbhcs-x)supporting
confidence: 88%
“…HeLa cells readily internalize nanoparticles of similar size to those used in this work, including 120 nm phospholipid vesicles, 50 nm gold nanoparticles and 18 nm silica nanoparticles. [35][36][37] Furthermore, EGFP fluorescence was stable within the cell in excess of two hours, suggesting that the PPN architecture protects the encapsulated components from intracellular proteases which may degrade the protein. Combined with PPN permeability and stability studies, these results strongly suggest the utility of polymerized PPNs for delivering enzymes and large molecular weight reporters to the intracellular environment and may represent a new paradigm for cellular analysis as well as diagnosis and treatment of disease.…”
Section: Resultsmentioning
confidence: 99%
“…[49] Furthermore, the ability to functionalize the surface of nanoparticles with large quantities of cell-recognition or other site-directing compounds makes them ideal agents for cell tracing. [50][51][52][53][54][55] In contrast to other solid nanoparticle biosensors, micro-and mesoporous silica provide two important unique advantages: 1) High porosity. The large surface areas and pore volumes allow the encapsulation/immobilization of large amounts of sensing molecules per particle for fast response times and low detection limits.…”
Section: Mesoporous Silica For Biosensing and Cell Tracingmentioning
confidence: 99%